2020
DOI: 10.2105/ajph.2019.305369
|View full text |Cite
|
Sign up to set email alerts
|

Demand for Self-Managed Medication Abortion Through an Online Telemedicine Service in the United States

Abstract: Objectives. To examine demand for abortion medications through an online telemedicine service in the United States. Methods. We examined requests from US residents to the online telemedicine abortion service Women on Web (WoW) between October 15, 2017, and August 15, 2018. We calculated the population-adjusted rate of requests by state and examined the demographics, clinical characteristics, and motivations of those seeking services, comparing those in states with hostile versus supportive abortion policy cli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
67
0
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 55 publications
(72 citation statements)
references
References 25 publications
2
67
0
3
Order By: Relevance
“…Respondents in these regions were more likely than those in other areas to report having had to temporarily close their clinics and to have canceled or postponed abortion services. This pattern of findings is consistent with results from a recent study that documented an increase in requests for medication abortion pills to an online service that supports people self‐managing abortions 23 . In addition, it appears that some preexisting restrictive abortion policies—such as requiring in‐person visits and banning telemedicine for abortion—have gotten in the way of abortion clinics being able to provide services in a manner that reduces COVID‐19 risks 24…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…Respondents in these regions were more likely than those in other areas to report having had to temporarily close their clinics and to have canceled or postponed abortion services. This pattern of findings is consistent with results from a recent study that documented an increase in requests for medication abortion pills to an online service that supports people self‐managing abortions 23 . In addition, it appears that some preexisting restrictive abortion policies—such as requiring in‐person visits and banning telemedicine for abortion—have gotten in the way of abortion clinics being able to provide services in a manner that reduces COVID‐19 risks 24…”
Section: Discussionsupporting
confidence: 85%
“…This pattern of fi ndings is consistent with results from a recent study that documented an increase in requests for medication abortion pills to an online service that supports people self-managing abortions. 23 In addition, it appears that some preexisting restrictive abortion policies-such as requiring in-person visits and banning telemedicine for abortion-have gotten in the way of abortion clinics being able to provide services in a manner that reduces COVID-19 risks. 24 Our fi ndings suggest that abortion clinics have experienced short-term fi nancial needs as well as challenges in retaining and supporting their workforce.…”
Section: Discussionmentioning
confidence: 99%
“…We suspect that self-managed abortion may become more common if clinic-based abortion care becomes more difficult to access, especially among women in south Texas where misoprostol may be more accessible due to the proximity to Mexico, and among poor women -who make up more than half of all abortion patients [1] and face barriers to accessing reproductive health care. Indeed, a recent study of requests to an online service that provides medication abortion to people living in countries where abortion is legally restricted, and does not provide services to the US, found that three-quarters of the more than 6000 requests from US residents received in a 10-month period in 2017-2018 were from residents of states hostile to abortion [19]. Reproductive health providers can play a key role in supporting the health and well-being of women interested in self-managing abortion for whom clinic-based care is difficult to obtain.…”
Section: Resultsmentioning
confidence: 99%
“… 1 People’s reasons for SMA are varied, and include both difficulty accessing facility-based abortion care and a preference for a more private or natural abortion experience. 2 , 3 , 4 …”
Section: Introductionmentioning
confidence: 99%